Use of rehydrated corn in feeding confined cattle (Research, Society and Development, 2025)
Rehydrated corn is one of the processing methods that makes the corn grain that has been broken and rehydrated more readily available in terms of starch, which is transformed into energy more quickly in the body. The objective of this study is to show the performance of animals on different diets with and without rehydrated corn grain. A documentary research was carried out from a direct source. The information was extracted from a database with the history of consumption and performance of animals in the Zona da Mata region of Rondônia. The data were compared between the performance of the two groups. The results were analyzed and a comparison was made to justify the use and efficiency of rehydrated grain in the diet, and the positive points of the diet with rehydrated corn grain, where the animals presented lower dry matter consumption, better biological efficiency and better feed conversion. A diet with greater starch availability obtains more energy, the animals take less time to reach chemical satiety, leading to a reduction in dry matter consumption.